Time series evaluation of ascitic syndrome condemnation at poultry abattoirs under Federal Inspection Service of Brazil (2010-2019) - Souza, Marina C.C.; Borges, Luiz Felipe N.M.; Nascimento, Yago F. [UNESP]; Costa, Letícia R.M. [UNESP]; Dias, Sthéfany C. [UNESP]; Ventura, Nayla K.O.; Freire, Isabela S.; Cossi, Marcus V.C. (FapUNIFESP (SciELO), 2021)
Over the last decade, Brazil registered a 10.56% increase in the number of poultry slaughtered in establishments registered under the “Serviço de Inspeção Federal” (SIF - Federal Inspection Service), as a result of technological advances in management, health and genetics applied to national aviculture. At slaughter, during post-mortem inspection, carcasses can be totally or partially condemned for various reasons, including ascitic syndrome. This syndrome has economic implications for the industry, in addition to being a problem for the health and welfare of poultry. The objective of this work was to evaluate the historical series (2010-2019) of partial and total condemnations of poultry carcasses due to ascitic syndrome in slaughterhouses registered under the SIF and located in the main poultry-producing states. Through official data, the condemnation occurrence index (COI) and the adjusted seasonal index (ASI) were calculated. The condemnation rate was 1,140 carcasses condemned, totally or partially, for ascitic syndrome for every 1,000,000 poultry slaughtered. The smallest and largest COIs were found in São Paulo (February 2010) and in Goiás (January 2017), respectively. The occurrence of condemnations for this syndrome was cyclical throughout the historical series, showing peaks of condemnation in all years evaluated, with the highest ASIs in July, August and September, and with rates varying between 1.24 and 1.54 in these months. Considering the period of pre-slaughter housing, the highest ASIs coincide with the coldest period of the year (May to August) for all analyzed states. The results show that ascitic syndrome is a growing problem in Brazil, with greater occurrence during the coldest months of the year, having a negative impact on animal health and the profitability of producers and industries in the poultry production chain.
Avaliação de um período histórico de condenações por síndrome ascítica em abatedouros de aves sob Serviço de Inspeção Federal do Brasil (2010-2019)
Keywords: Ascitic syndrome; Brazil; Condemnations; Federal inspection service; Poultry slaughter